Psychosocial stress in children with Tourette syndrome and chronic tic disorder - Chiew Yin Tan; Nan-Chang Chiu; Yi-Hong Zeng; Jia-Yun Huang; Ruu-Fen Tzang; Hui-Ju Chen; Yi-Jie Lin; Fang-Ju Sun; Che-Sheng Ho (Pediatrics and Neonatology)
Background: This study aimed to understand the longitudinal relationship between psychosocial stress with tic exacerbation in children with Tourette syndrome (TS) and chronic tic disorder. Methods: Consecutive ratings of tic severity as well as child and parental reports of psychosocial stress were obtained for 373 children (296 males, 77 females; mean age 9y 5mo; SD 3y 3mo) with TS and chronic tic disorder between January 2018 and December 2020. The Yale Global Tic Severity Scale (YGTSS) global severity score, total tic score, and impairment rating were calculated. The stressful events and YGTSS measurements were used and treated as time-varying variables in the analyses. Models that controlled for non-independence among the repeated observations using a random intercept and random slope model were employed. Each participant was treated as a random factor in the modelling. Results: Family-related stress, personal relationship stress and school-related stress were independently associated with increasing YGTSS global severity, total tic score, and impairment rating over time. An increased number of stressful events were associated with increased severity of tics. Conclusion: Family, personal relationships, and school-related stress were consistently associated with the exacerbation of tics. Managing these stressful events is important in the treatment of TS and chronic tic disorder.